Adapting Techno-Pedagogy: A Comparative Study of Localized Teacher Support Systems in Rural Sri Lanka and Tamil Nadu, India - Paunanthie, A.; Tholappan, A.; Jayabharathi, S. (University of Colombo, 2025)
The recent global drive for digital education has unveiled stark discrepancies between urban and rural education, especially in developing countries. This paper compares the challenges and responses to the process of adapting techno-pedagogy through local teacher support networks in rural Sri Lanka and Tamil Nadu, India. The paper, which draws on existing literature and reports, applies the Technological Pedagogical Content Knowledge (TPACK) framework to show that the problem is not one of hardware distribution, but of contextually relevant professional development. The study finds that both regions face important common obstacles, such as a lack of infrastructure, unreliable internet connectivity, and teacher training that is not contextualized. But the nature of their localization efforts varies: while Sri Lanka's localization often takes the form of piecemeal, multi-stakeholder initiatives with an emphasis on basic digital literacy, Tamil Nadu's localization is more likely to be achieved through large-scale, state-led initiatives like the DIKSHA platform. Among the successful strategies in both contexts are the importance of differentiated and individualized teacher support, the influence of Professional Learning Communities (PLCs) as a collaborative support system, and the success of blended learning. The article concludes by suggesting a multi-tiered model of localized support that highlights the importance of diagnostic needs assessment, school-based mentorship, and the development of teacher agency. Among the lessons learned from this comparison is the need for support systems for sustainable technopedagogical integration in rural areas to not be only transplanted but grounded in local realities.
Keywords: TPACK; Rural Education; Digital Divide; Localization